O protagonismo feminino nas lutas por liberdade e igualdade social: La Tribuna, de Emilia Pardo Bazán e Mariana Pineda, de Federico García Lorca - Andreta, Bárbara Loureiro (2021)
The current thesis aims to compare the novel La Tribuna by Emilia Pardo Bazán with the play Mariana Pineda by Federico García Lorca, analyzing the political-historical connections present in such works. Both literary works stand out because they present a strong feminine protagonism in moments of intense social and political movements in Spanish history. Considering this, it was elaborated the research hypothesis that women in the XIX century had a bigger political protagonism than the one that is normally given to them by the historical canon or by the literary canon itself. To reach such objectives, it was carried out an analytical study of the corpus regarding the theories of comparative literature, applying intertextual and interdisciplinary comparative assumptions and, in theoretical terms, the feminist literary criticism was used as a reference. The theoretical studies selected as references were Carvalhal (2006), Golubov (2012), Rago (2005) and Charnon-Deutsch (2003, 2004). Thematology was chosen as the methodology because this work is analyzing two distinct literary genres. This research is relevant because it rescues the role and performance of women in the literature in moments of intense social movements in Spain as well as revisiting cultural, social and political facts that guided each one of the authors to write works highlighting the women's struggle for freedom and equality. The analysis of the works allowed identifying that in La Tribuna and in Mariana Pineda, despite living big loves, the protagonists got involved in the political struggle because they believed in a revolutionary ideal. The authors transformed their writing in a place to report injustices lived by the nineteenth-century Spanish women and besides, it became a prominent space for women’s struggles and demands. This way, through their works, Emilia Pardo Bazán and Federico García Lorca highlighted that women were also agents in the Spanish history construction, giving emphasis to their roles.